Upaya Pencegahan Penyakit Degeneratif Melalui Edukasi Kesehatan Pada Lansia di Desa Penggalaman Kecamatan Martapura Barat - Nurbidayah Nurbidayah; Fairuz Yaumil Afra; Muhammad Saufi; Bandawati Bandawati (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Elderly is known as someone who is older than 60 years. The elderly have a greater risk of disease, especially degenerative diseases. A decrease in physical activity, lifestyle and food consumption is one of the factors causing the development of this disease. Therefore, it is better if it is detected early by carrying out a health examination and having good knowledge about the disease, so that it can prevent the disease from becoming a complication and reduce dangerous risks. The aim of this activity is to achieve preventive efforts to reduce the risk of degenerative diseases that can cause complications. The method used is counseling with the stages carried out namely field observation, coordination with cadres, filling out questionnaires regarding knowledge about degenerative diseases and awareness of health checks, carrying out health checks, and outreach. The results of the activity showed that the community was very enthusiastic about carrying out health checks and taking part in socialization. The results of measuring community knowledge show that 48.5% of the community is in the good category, 27.3% is sufficient and 24.2% is poor and 32 people have good awareness.